Prospects And Challenges Post the Conversion of Conventional Banks To Islamic: A Case Study of Islamic Rural Bank (BPRS) Rizky Barokah - Angraini, Frahmi Laila; Mihajat, Muhammad Iman Sastra (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
Since the passage of Law No. 21 of 2008 on Islamic banking, the development of Islamic banks in Indonesia has grown significantly. Converting conventional banks to Islamic banks is one of the strategies supported to increase the accessibility of Islamic banking. Therefore, this study explores the opportunities and challenges faced by Islamic Rural Bank (BPRS) Rizky Barokah after its conversion. This study used a qualitative descriptive approach collecting data through observation, interviews, documentation and literature reviews. The results of the research show that BPRS Rizky Barokah’s conversion offers opportunities that support the bank’s developmet, such as an increased customer improved financial stability, enhanced reputation, greater operational efficiency and the creation of unique sharia-compliant products. However, challenges include low Islamic financial literacy, product innovation to meet customer demands, customer retention, limited expertise in Islamic finance that does not meet market expectations and ensuring sharia compliance in all operations. Despite these challenges, BPRS Rizky Barokah has implemented effective strategies to address them and optimize the benefits of conversion.